Mechanical behaviors of surrounding rock and supporting structure of shallow-buried unsymmetrical pressure tunnel crossing soil–rock interface - Hu, Zhinan; Zhang, Ji; Wang, Yonggang; Wang, Yunfei (Frontiers in Earth Science, 2023)
Shallow bias tunnels are sensitive at the entrance section, where the existence of soil–rock interface (SRI) results in more complex deformation of surrounding rock and supporting structure. This study investigates the mechanical properties of surrounding rock and supporting structure of a shallow-buried bias tunnel crossing the SRI by a combination of model tests and numerical simulations. A shallow-buried biased tunnel with significant cracking at its entrance section is selected in southwest China. The plastic zone distribution, deformation, and pressure of surrounding rock, as well as the stress and deformation of supporting structure, are analyzed under different conditions with the tunnel vault, arch haunch, arch spring, and wall foot crossing the SRI. The test and numerical results show that the internal force of the lining structure is the largest at the left arch haunch and the right arch spring, with cracks occurring in the project. The surrounding rock and supporting structure are most prominently influenced by the arch haunch and arch spring crossing the SRI among different positions of the tunnel. The supporting structure is subjected to stress in three modes: there is mainly shearing when the tunnel vault passes through the SRI, extrusion and shearing co-exist when the tunnel arch haunch and arch spring pass through the SRI, and extrusion is dominant when the tunnel wall foot passes through the SRI. Inserting grouting steel pipes perpendicular to the SRI on the deep-buried side of the tunnel can effectively control the deformation of surrounding rock and the stress of supporting structure.